FIIL MAZID DI DALAM AL QURâAN (STUDI MORFOLOGI BAHASA ARAB TERHADAP QURâAN SURAT YASIN) - mufid, miftahul (Institut Agama Islam Sunan Giri Bojonegoro, 2017)
language is something that is very important in life because without the language of communication will not occur. Language has a unique arrangement in each region. And the most interesting part of any language Arabic is written in the Quran because the book of Quran is a Book given by God to the Prophet Muhammad. other than that Quran is a miracle possessed by the prophet Muhammad. From here we as human beings are given intellect by God obligatory to study scripture. And the object of study This is the letter Yasin al-qurâan, while the focus of research is the scientific study of morphological / sharf namely in verb mazid in this letter. This study findings that in the letter contained Yasin Nineteen words that have a shape verb mazid